(untitled) (Applied Biological Research, 2023)
Jammu and Kashmir has enormous fisheries potential due to its vast area and quantity of freshwater sources. The UT has rivers like Chenab, Tawi, Ravi, and Jhelum, as well as lakes including Dal lake, Wular lake, Manasbal lake, and Surinsar, Manasar lake. The purpose of this study is to summarize some of the key studies done on the Ichthyofaunal diversity of numerous water bodies in the Jammu region, as well as to create an inventory of the region’s Ichthyofauna while analyzing the dominant and least prominent species. The examination undertaken revealed the presence of 158 distinct fish species belonging to 10 orders, with Cypriniformes being the most dominating order and Cyprinidae being the most significant contributing family, while Anabantiformes and Clupeiformes were in traces. Furthermore, analysis of conservation status of the fauna revealed that, majority of the species in the region have a conservation status of "Least Concern", while a few species are endangered or vulnerable. Analysis of fish fauna of the region’s major lotic water bodies finds that river Ravi has the largest fish diversity; however, a comparative analysis of fish fauna reveals that diversity is diminishing in the region necessitating extensive conservation strategies.